Transcatheter aortic valve implantation in patients with small aortic annuli using a 20 mm balloon-expanding valve. Issue 2 (17th August 2016) - Puri, Rishi; Byrne, Jonathan; Muller, Ralf; Baumbach, Hardy; Eltchaninoff, Helene; Redwood, Simon; Cheema, Asim; Dubois, Christophe; Ihlberg, Leo; Wijeysundera, Harindra C; Cerillo, Alfredo; Götberg, Matthias; et al.
Abstract : Background: While transcatheter aortic valve implantation (TAVI) is established for treating high-operative risk surgical aortic valve replacement candidates, until recently the smallest transcatheter heart valve (THV) measured 23 mm, posing greater risk for annular rupture and THV failure in patients with aortic stenosis (AS) with small aortic annuli (≤20 mm). Objectives: In the setting of a multicentre registry, we report on the safety, efficacy and early clinical outcomes of the SAPIEN XT 20 mm balloon-expanding THV. Results: Among TAVI 55 recipients (n=30 for native AS, n=25 for a valve-in-valve procedure (V-in-V)), median age and Society of Thoracic Surgeons score were 85 (81 to 87) years and 7.8 (4.7 to 12.4)%, respectively. Mean and minimum annular diameters were 19±1 and 17±2 mm, respectively, in native patients with AS, and 17±1 mm (internal diameter) in V-in-V recipients. Successful device implantation rate was 96%, with no procedural-related death. Overall in-hospital-30-day death, stroke and major bleeding rates were 5%, 2% and 9%, respectively. In native AS TAVI recipients, mean transaortic gradient decreased from 54±20 to 12±5 mm Hg (p<0.001), and from 45±17 to 24±8 mm Hg (p<0.001) in V-in-V recipients. Severe prosthesis-patient mismatch (PPM) rates were 10% and 48% in native AS and V-in-V TAVI recipients, respectively (p=0.03). Post-TAVI, the rate of moderate aortic regurgitation was 7% and 0% in native AS and V-in-V TAVI recipients, respectively. Conclusions: TAVI with the 20 mm SAPIEN XT THV appears safe and technically feasible, with acceptable short-term clinical outcomes and low rates of severe PPM in those with native AS.